INTEGRASI PENGENDALIAN PROSES SEBAGAI UPAYA PENCEGAHAN RISIKO KESELAMATAN KERJA DI INDUSTRI KIMIA - Riny Yolandha Parapat; Aldi Muhamad Rizky; Nisa Wahyu Septiyaningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
The chemical industry is a sector with a high level of occupational safety risk due to the use of hazardous materials, extreme operating conditions, and the complexity of the processes involved. Therefore, systematic and integrated efforts are required to prevent occupational safety risks. One of the approaches that plays an important role in this effort is process control. This paper discusses the integration of process control as an effort to prevent occupational safety risks in the chemical industry. The discussion focuses on the relationship between process control and occupational safety, the concept of integrating process control with safety systems, and the strategies for its implementation in chemical industry activities. The integration of process control includes the regulation of critical variables such as temperature, pressure, flow rate, and level, supported by control systems, alarms, interlocks, and safe operating limits as part of process risk management. A review of the literature shows that the implementation of integrated process safety systems, including process control and safety management, can significantly reduce the number of process safety incidents. For example, industry reports compiled by the American Chemistry Council indicate that the implementation of process safety programs and integrated control systems has reduced process safety incidents by approximately 48% since 2000 among companies participating in the Responsible Care program. In addition, other studies analyzing industrial accidents indicate that companies with low levels of process safety management implementation have a much higher probability of accidents, and most major accidents occur in facilities with inadequate process safety systems. This demonstrates that the presence of effective process control systems and safety management plays a significant role in reducing industrial accident risks. Therefore, the integration of process control with occupational safety systems can prevent abnormal operating conditions, reduce the potential for accidents caused by human error, and improve the reliability and safety of chemical plant operations. Process control integration thus becomes a key element in supporting the achievement of a safe and sustainable working environment in the chemical industry.